Antibiotic resistance and antibiotic sensitivity based treatment in Helicobacter pylori infection: advantages and outcome. Issue 5 (1st May 2001) - Street, M E; Caruana, P; Caffarelli, C; Magliani, W; Manfredi, M; Fornaroli, F; de'Angelis, G L
Abstract : AIMS: To compare two strategies for the eradication of Helicobacter pylori infection. METHODS: Groups 1 and 2 each consisted of 75 consecutive patients. Patients in group 1 were treated with two antibiotics based on antibiotic susceptibility testing; those in group 2 received amoxycillin and clarithromycin for eight days, together with either ranitidine or omeprazole. Eradication rate was assessed in both groups six months after treatment. RESULTS: In group 1, H pylori grew in culture in 63/75 cases. Susceptibility testing showed that 35/63 isolates were resistant to metronidazole, 10/63 to clarithromycin, 2/63 to ampicillin, 1/63 to tetracycline, and 5/63 to both clarithromycin and metronidazole. In group 1 the infection was eradicated in 96% of the initial 75 subjects, and in 98% of the subjects treated according to the antibiotic assay (62/63). As two patients were lost at follow up the overall eradication rate was 99%. In group 2, eradication was achieved in 61/75 subjects (81%). This was significantly lower than the percentage of eradication observed in group 1 (81% versus 99%). CONCLUSIONS: Antibiotic susceptibility tests are useful in childhood as a very high percentage of subjects are cured. This approach is costly, but selective antibiotic treatment contributes to limit further development of antibiotic resistance, and money is saved in terms of reinvestigation and further repeated treatments.